2019
DOI: 10.1080/13102818.2019.1578690
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and evaluation of chitosan-based nanoparticles as CpG ODN carriers

Abstract: Chitosan-based particles are desirable materials for drug delivery because of their muco-adhesiveness in tissues, biocompatibility, low toxicity and effectiveness in antigen transport. It is still a challenge to prepare chitosan-based particles with high stability and by an effective method. Here we developed chitosan-based nanoparticles for the delivery of toll-like receptor 9 ligands, cytosine-phosphate-guanine oligodeoxynucleotides (CpG ODNs), which can induce the change from Th-2 type to Th-1 type immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Our DLS results are comparable to the average size of CSNPs reported in literature, i.e. 189 and 197 nm by Khan et al 32 , 216 nm by Agarwal et al 33 , and size range of 135-729 nm by Rasaee et al 34 and 6.5-1331.2 nm by Iswanti et al 35 . TEM of AMCSNPs in our study revealed a spherical shape with a smooth surface, which was also reported by Da Silva et al 21 .…”
Section: Discussionsupporting
confidence: 90%
“…Our DLS results are comparable to the average size of CSNPs reported in literature, i.e. 189 and 197 nm by Khan et al 32 , 216 nm by Agarwal et al 33 , and size range of 135-729 nm by Rasaee et al 34 and 6.5-1331.2 nm by Iswanti et al 35 . TEM of AMCSNPs in our study revealed a spherical shape with a smooth surface, which was also reported by Da Silva et al 21 .…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, in this survey, ALL-loaded chitosan/ sodium tripolyphosphate nanoparticles (ALL-loaded CS/STPP NPs) were prepared by ionotropic gelation technique and thoroughly characterized. A full 2 4 factorial design was adopted using four independently controlled parameters (ICPs). Comprehensive characterization, in vitro evaluations as well as antiulcerogenic activity study against ethanol-induced gastric ulcer in rats of the optimized NPs formula were conducted.…”
Section: Formulation Optimization and Characterization Of Allantoin-loaded Chitosan Nanoparticles To Alleviate Ethanol-induced Gastric Ulmentioning
confidence: 99%
“…Such combination was asserted to be non-toxic and hindered the possibility of drug degradation. Moreover, CS-NPs are positively-charged with mucoadhesive as well as permeation enhancing properties, thus facilitate opening of the epithelial tight junctions [2][3][4] .…”
Section: Formulation Optimization and Characterization Of Allantoin-loaded Chitosan Nanoparticles To Alleviate Ethanol-induced Gastric Ulmentioning
confidence: 99%
See 2 more Smart Citations